The ATLAS Public Web Pages: Online Management of HEP External Communication Content. Issue 5 (December 2015) - Goldfarb, S; Marcelloni, C; Phoboo, A Eli; Shaw, K
Abstract: The ATLAS Education and Outreach Group is in the process of migrating its public online content to a professionally designed set of web pages built on the Drupal [1] content management system. Development of the front-end design passed through several key stages, including audience surveys, stakeholder interviews, usage analytics, and a series of fast design iterations, called sprints. Implementation of the web site involves application of the html design using Drupal templates, refined development iterations, and the overall population of the site with content. We present the design and development processes and share the lessons learned along the way, including the results of the data-driven discovery studies. We also demonstrate the advantages of selecting a back-end supported by content management, with a focus on workflow. Finally, we discuss usage of the new public web pages to implement outreach strategy through implementation of clearly presented themes, consistent audience targeting and messaging, and the enforcement of a well-defined visual identity.